Causes and predictors of 30-day readmissions in patients with cardiogenic shock requiring extracorporeal membrane oxygenation support. Issue 4 (April 2020) - Tashtish, Nour; Al-Kindi, Sadeer G; Karnib, Mohamad; Zanath, Erica; Mitchell, Steven; Di Felice, Christopher; Zacharias, Michael; Oliveira, Guilherme H; Medalion, Benjamin; Lytle, Francis; Elamm, Chantal
Background: Cardiogenic shock is associated with significant mortality, morbidity, and healthcare cost. Utilization of extracorporeal membrane oxygenation in cardiogenic shock has increased in the United States. We sought to identify the rates and predictors of hospital readmissions in patients with cardiogenic shock after weaning from extracorporeal membrane oxygenation. Methods: Using the 2016 Nationwide Readmission Database, we identified all patients (⩾18 years) with cardiogenic shock (ICD-10 CM R57.0) that have been implanted with extracorporeal membrane oxygenation (ICD-10-PSC of 5A15223) and were discharged alive (January–November 2016). We explored the rates, causes, and predictors of all-cause readmissions within 30 days. Results: Out of 69, 040 admissions with cardiogenic shock, 1641 (2.4%) underwent extracorporeal membrane oxygenation (581 were implanted during or after cardiac surgery). A total of 734 (44.7%) patients of all extracorporeal membrane oxygenations survived to discharge, and 661 were available for analysis. Out of those, 158 (23.9%) were readmitted within 30 days of discharge. More than 50% of these readmissions happened within the first 11 days. Out of 158 patients who were readmitted, 12 (7.4%) died during the readmission hospitalization. Leading causes of readmission were cardiovascular (31.6%) (heart failure: 24.1%, arrhythmia: 20.6%, neurovascular: 10.3%, hypertension: 10.3%, and endocarditis: 6.8%), followed by complications of medical/device care (17.7%), infection (11.3%), and gastrointestinal/liver (10.1%) complications. Factors associated with readmissions include the following: discharge to skilled nursing facility or with home healthcare (odds ratio: 2.10; 95% confidence interval: 1.18–3.74), durable ventricular assisted device implantation, asthma, and chronic liver disease. Conclusion: Patients with cardiogenic shock who underwent extracorporeal membrane oxygenation had a readmission rate. Identifying patients at high risk of readmissions might help improve outcomes.